Understanding the Trend of Digital Da'wah Among Muslim Housewives in Indonesia - Aslan, Aslan; Shiong Pong, Kok (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2023)
This paper describes the trend of digital da'wah among Muslim homemakers in Indonesia. The author observes that the trend of da'wah electronically, especially on social media, is getting more grounded among homemakers. So to convince our observation, the author finally searches various literary sources, especially scientific publications in broadcasting Islamic da'wah among Muslim households through various social media platforms. The data will not mean much without going through an in-depth study process that involves various methods such as data coding and in-depth interpretation of critical data and evaluation. The authors can conclude that the findings are capable and relevant to answer this research problem with high quality and accountability. After discussing the findings, the authors finally understand that the digital trend of Islamic da'wah among Muslim homemakers in Indonesia has progressed through social media and online video media. It is hoped that this finding will become new insights and support similar studies in the future.